2012
DOI: 10.1089/jmf.2011.0056
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofPassiflora edulis(Yellow Passion) on Serum Lipids and Oxidative Stress Status of Wistar Rats

Abstract: The aim of this study was to evaluate the effects of Passiflora edulis f. flavicarpa Degener (yellow passion) juice on the lipid profile and oxidative stress status of Wistar rats. Adult male Wistar rats were divided in two groups (n = 8 animals per group): the control group, which received water, and the treated group, which was given P. edulis juice (1,000 mg/kg). Both groups received by gavage treatment twice a day for 28 days. The treated group showed an increased high-density lipoproteincholesterol level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
1
8
0
3
Order By: Relevance
“…De Souza et al . () showed that the treatment of normotensive Wistar rats with Passiflora edulis juice decreased TBARS levels; however, this study did not investigate the effects of the juice on blood pressure. Furthermore, the present study found lower GSH content and higher TBARS levels in SHR compared to Wistar rats, which is consistent with other studies describing that hypertensive patients show greater oxidative stress with higher reactive species than that present in the normal oxidative stress response (Houston, ) and that the renal oxidative stress of SHR is higher than that of normotensive rats (Biswas and De Faria, ).…”
Section: Discussionmentioning
confidence: 79%
“…De Souza et al . () showed that the treatment of normotensive Wistar rats with Passiflora edulis juice decreased TBARS levels; however, this study did not investigate the effects of the juice on blood pressure. Furthermore, the present study found lower GSH content and higher TBARS levels in SHR compared to Wistar rats, which is consistent with other studies describing that hypertensive patients show greater oxidative stress with higher reactive species than that present in the normal oxidative stress response (Houston, ) and that the renal oxidative stress of SHR is higher than that of normotensive rats (Biswas and De Faria, ).…”
Section: Discussionmentioning
confidence: 79%
“…58 The consumption of P. edulis juice did not improve antioxidant enzyme status but did decrease the blood TBARS levels, indicating that the antioxidant capacity may be related to the addition of exogenous antioxidants present in the juice. 59 However, although Rudnicki et al 60 did not observe changes in liver MDA levels, the consumption of the hydroalcoholic extracts of both P. alata and P. edulis leaves had significant protective effects against carbonyl protein formation and advanced glycation end-products. In addition, those authors observed a linear relationship between total phenolic content and total antioxidant activity, indicating that these compounds might be the major contributors to animal's antioxidant activities.…”
Section: Resultsmentioning
confidence: 92%
“…The PFJ used in this study was a commercially available PFJ produced from purple passion fruits at Doi Kham Food Products Co. Ltd., (Chiang Rai, Thailand). The concentration of PFJ was 50% (50 g/100 mL) according to a previous study by de Souza Mda et al (2012), which reported productive effects of PFJ supplementation at 1 g/kg on improving levels of plasma lipid and oxidative stress. One hundred mL of the juice provided 55 kcal, consisting of 12.5 g sugars, 1 g other carbohydrate, <0.5 g dietary fibers, and 10 g sodium.…”
Section: Methodsmentioning
confidence: 99%